Biodiversity and composition of lepidopterans at Universiti Teknologi MARA (UiTM) Pahang, Jengka Campus / Mohamad Azam Akmal Abu Bakar … [et al.] - Abu Bakar, Mohamad Azam Akmal; Mohd Zaki, Muhammad Luqman; Lokman, Mohd Syarafuddin; Nazirie, Ahmad Izzudin; Zali, Haziq Iqmal; Ahmad Lutfy, Siti Nuruljannah (Universiti Teknologi MARA, Sabah, 2021)
This study was conducted to record the lepidoptera species at UiTM Pahang in July and August 2019. A total of 261 Lepidoptera species belonging to 21 species from four families were recorded. Nymphalidae (54%) was found to be the most dominant followed by Pieridae (31%), whereas Hesperiidae (9.2%) and lastly Papilionidae (0.06%) were less common. There were 12 species of Nymphalidae collected followed by 4 species of Pieridae, 4 species of Papilionidae and 1 species of Hesperiidae sampled in three study sites comprising forest area, plantation area and urban area. The diversity analysis (Shannon-Wiener index, Dominance index and Evenness index) were used to analyse the biodiversity of the species. The findings of this study contributed to the local fauna database which can be useful for future researchers.